Factors associated with non-adherence to angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in older patients with peripheral arterial disease - Wawruch, Martin; Petrova, Miriam; Tesar, Tomas; Murin, Jan; Schnorrerova, Patricia; Paduchova, Martina; Celovska, Denisa; Havelkova, Beata; Trnka, Michal; Alfian, Sofa D.; Aarnio, Emma (Frontiers in Pharmacology, 2023)
Introduction: As in other chronic conditions, medication adherence is important in the treatment of peripheral arterial disease (PAD). Our study aimed at a) analysing non-adherence to angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in groups of older ACEI and ARB users with PAD, and b) identifying characteristics associated with non-adherence. Methods: We focused on the implementation phase of adherence (i.e., after treatment initiation and before possible discontinuation of treatment). The study cohort included ACEI/ARB users aged ≥65 years in whom PAD was newly diagnosed during 2012. Non-adherence was defined as Proportion of Days Covered (PDC) < 80%. Results: Among 7,080 ACEI/ARB users (6,578 ACEI and 502 ARB users), there was no significant difference in the overall proportion of non-adherent patients between ACEI and ARB users (13.9% and 15.3%, respectively). There were differences in factors associated with non-adherence between the groups of persistent and non-persistent (i.e., discontinued treatment at some point during follow-up) ACEI and ARB users. Increasing age, dementia and bronchial asthma were associated with non-adherence in persistent ACEI users. General practitioner as index prescriber was associated with adherence in the groups of non-persistent ACEI users and persistent ARB users. Conclusion: Identified factors associated with non-adherence may help in determining the groups of patients who require increased attention.